Association of rs610932 and rs670139 Polymorphisms in the MS4A Gene Cluster with Alzheimer’s Disease: An Updated Meta-analysis - Zhu, Ruixia; Liu, Xu; He, Zhiyi (Current Alzheimer Research, 2017)
Background: Two large-scale genome-wide association studies have identified rs610932 and rs670139 polymorphisms within the MS4A gene cluster as being significantly associated with susceptibility to Alzheimer’s disease (AD) in those with European ancestry. A number of studies have focused on the association between MS4A gene variants and AD in Caucasian and East Asian populations. However, the results remain inconsistent owing to the small sample size in each study. Objective: We performed a meta-analysis to explore whether rs610932 and rs670139 polymorphisms are associated with susceptibility to AD. Method: 19 studies with 34,119 cases and 56,956 controls concerning rs610932 and 18 studies with 33,622 cases and 55,322 controls concerning rs670139 were included in this meta-analysis by searching the PubMed, MEDLINE, and AlzGene databases. Results: Our results showed significant associations between rs610932 and rs670139 polymorphisms and AD in the pooled population using an additive model. In subgroup analysis, we also identified a significant association of rs610932 in the Asian population under additive [odds ratio=0.82, 95% confidence interval 0.69-0.99, p=0.03] and dominant models (odds ratio=0.82, 95% confidence interval 0.72-0.95, p=0.006), but not under a recessive model. However, no association was found between rs670139 and AD patients using all three of these models in the Asian population. Conclusion: Our results suggest that the rs610932 polymorphism contributes to AD susceptibility in Caucasian and Asian populations. To our knowledge, this is the largest meta-analysis to investigate the association between MS4A gene polymorphisms and AD in Asian and European populations.
Keywords: MS4A gene cluster